Balancing Birr al-Wālidayn and Family Obligations: A Maqāṣid al-Sharīʿah Perspective on Sandwich Generation Families - Intan Juana; Abdul Halim (Kartika: Jurnal Studi Keislaman, 2026)
The sandwich generation phenomenon has become a socio-economic issue growing within contemporary families, particularly among households facing economic instability. Individuals in this category bear the dual responsibility of supporting both their nuclear family and their elderly parents, thus facing a dilemma in determining financial priorities. This study analyzes the practice of financial priority among sandwich generation families in Sukorejo Village, Jember, from the perspective of Maqāṣid al-Syarī'ah. Using a qualitative empirical method through interviews, observation, and documentation, the data were analyzed using the Miles, Huberman, and Saldaña interactive model. The findings reveal three main priority patterns: first, prioritizing parents due to the strong commitment to birr al-wālidayn and cultural values of filial piety; second, prioritizing the nuclear family due to urgent daily needs, children's education, and household welfare; and third, attempting to balance support for both generations despite limited and unstable income. From the Maqāṣid al-Syarī'ah perspective, these practices reflect efforts to simultaneously realize ḥifẓ al-dīn (protection of faith), ḥifẓ al-nafs (protection of life), ḥifẓ al-nasl (protection of progeny), and ḥifẓ al-māl (protection of property). The study concludes that financial priority among sandwich generation families cannot be understood as a binary choice between filial piety and responsibility toward the nuclear family, but rather as a process of balancing interconnected obligations to achieve maṣlaḥah (public good). This research contributes to the development of Islamic family law studies through a maqāṣid-based understanding of financial responsibilities in multigenerational families.